Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3892/etm.2021.10489
|View full text |Cite
|
Sign up to set email alerts
|

Fas regulates the apoptosis and migration of trophoblast cells by targeting NF‑κB

Abstract: Placental trophoblast apoptosis is a major pathological feature of preeclampsia. Fas has been reported to be highly expressed in the placentas of patients with preeclampsia. However, the role and underlying mechanisms of Fas in the pathogenesis of preeclampsia have not been elucidated. In the present study, the expression of Fas in JAR human choriocarcinoma cells was overexpressed and knocked down to determine the function and possible mechanism of Fas in trophoblast cells in the progression of preeclampsia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Downregulation of MyoD mediates the expression of miR-1 and miR-206, activates transcription of the anti-apoptotic proteins B-cell lymphoma 2 (BCL-2) and B-cell lymphoma-extra large (BCL-xL), and enhances myoblast survival [41]. Apoptosis is an active process of programmed death that involves the activation, expression and regulation of a series of genes, including BAK1, BID, FAS, and Caspase9 [42][43][44]. The apoptosis-promoting BAK1 and BID proteins can commit a cell to programmed death by permeabilizing the outer mitochondrial membrane (OMM) and subsequently initiating the caspase cascade [42,45].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of MyoD mediates the expression of miR-1 and miR-206, activates transcription of the anti-apoptotic proteins B-cell lymphoma 2 (BCL-2) and B-cell lymphoma-extra large (BCL-xL), and enhances myoblast survival [41]. Apoptosis is an active process of programmed death that involves the activation, expression and regulation of a series of genes, including BAK1, BID, FAS, and Caspase9 [42][43][44]. The apoptosis-promoting BAK1 and BID proteins can commit a cell to programmed death by permeabilizing the outer mitochondrial membrane (OMM) and subsequently initiating the caspase cascade [42,45].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the p53 expression corresponds to the hypoxia that is generated in the placenta by PE, at least in vitro [ 52 ], and has implications in the intrauterine growth restriction [ 53 ]. The FAS, on the other hand, is involved in mediating the maternal immune response, in cell remodeling, and in cell proliferation [ 51 , 54 ]; therefore, the increase in this protein is a direct indicator of placental apoptosis, which is a common finding in PE [ 55 , 56 ]. Although these findings are not completely comparable with ours, the under expression of the apoptosis-related genes may be due to the fact that the placental biopsies that were used in this study came from the rats that were at the end of their pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl‐2 is an antiapoptotic protein, the elevated level of which implies the promotion of cell apoptosis. Therefore, the degree of apoptosis can be directly reflected by the changed levels of Bcl‐2 and Bax 35 . Caspase‐3 belonging to the protease family exerts crucial functions in both extrinsic and intrinsic apoptotic processes 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the degree of apoptosis can be directly reflected by the changed levels of Bcl-2 and Bax. 35 Caspase-3 belonging to the protease family exerts crucial functions in both extrinsic and intrinsic apoptotic processes. 36 It has been reported that Pae could inhibit cell apoptosis in high glucose and palmitic acid-induced endothelial cells 37 and Pae activates the class III PI3K/Beclin-1 pathway to inhibit apoptosis of vascular smooth muscle cells.…”
Section: Pae Attenuates Placental Inflammation By Inhibiting the Jak2...mentioning
confidence: 99%